Station Rotation Model: Effects on the Achievement Level of Grade 10 Learners in Circles - Ferrylou Guadiario; Douglas Salazar (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to determine the effect of the Station Rotation Model on Grade 10 learners’ achievement levels in the topic of circles by measuring changes in their pretest and posttest scores and gathering insights from their learning experiences. Methodology: One-group pretest–posttest pre-experimental design was employed. Tools included a researcher-made 30-item test, interview guide questionnaire, CK-12 Flexbook, Edpuzzle, Quizizz, GeoGebra, and Padlet. Google Classroom managed all materials. Wilcoxon Signed-Rank test, Shapiro-Wilk test, and thematic analysis for qualitative responses were used to analyze the data. Main Findings: Learners’ achievement improved from a “Beginning” mean score of 11.85 to a “Developing” mean score of 21.54 after the intervention. The Wilcoxon Signed-Rank Test revealed a significant difference (p = 0.001), and twenty-five students demonstrated score improvement. Qualitative data emphasized the following: that the model allowed collaborative learning, increased engagement through interactive activities, and valued on the support of teachers in clearing up complex issues. Novelty/Originality of this study: This study uniquely applies a daily structured Station Rotation Model with clearly defined teacher-led, collaborative, and online stations specifically for Grade 10 circles. It integrates multiple digital tools and immediate peer interaction, offering a detailed model not previously examined in mathematics. It provides more evidence of station rotation model's efficiency in teaching geometry.